FPGA based maximum power point tracking controller for photovoltaic system - Mahmood Almuhaya, Mukarram Abduljalil (2013)
Nowadays, PV cell which is known as a photovoltaic is one of the most important parts in electrical field to convert photolight to voltage and current at the desired output voltage and frequency by using varies control techniques. This project presents design and implementation of FPGA Based Maximum Power Point Tracking (MPPT) Controller for Photovoltaic system. The MPPT controller is employed to control and get Maximum Power Point (MPP) of the output voltage reference from the source. Altera DE2 board devices are used as a controller for the implementation of the MPPT system. The simulation of this FPGA based MPPT controller is designed and implemented using Quartus II VHDL software tools. The results shown, the same signal obtained from Matlab simulink software as compared with Quartus II. It has been observed that the designed system has been successfully extracting the MPP from the pseudo sources used in the simulations. The system has been evaluated in sunny day and partially shaded conditions to analyze the respective outputs in these conditions.